Synthesis-Dependent Microhomology-Mediated End Joining: A Unifying Model For Multiple DNA Double Strand Break Repair Outcomes. - Yu, Amy. (2017)
Abstract: DNA double-strand breaks (DSBs) are repaired by homology-directed repair or non-homologous end joining. End-joining repair can be classified as classical non-homologous end joining, which requires DNA ligase 4, or "alternative" end joining (alt-EJ), which does not. The mechanism of alt-EJ is largely uncharacterized. We show that Drosophila melanogaster DNA polymerase theta (pol theta), encoded by the mus308 gene, plays a role in alt-EJ. In pol theta mutants, end joining is impaired, creating large deletions. Sequencing suggests that pol theta promotes the use of long microhomologies during alt-EJ. These results suggest a mechanistic link between alt-EJ and interstrand crosslink repair. Alt-EJ repair frequently correlates with junctional microhomology but also produces junctions without microhomology, and the role of microhomology in alt-EJ remains unclear. To investigate this, we examined inaccurate repair of an I-SceI DSB with few nearby microhomologies in Drosophila. Lig4 deficiency did not affect junctional microhomology, but significantly increased insertions. Many insertions appeared templated. Based on sequence analysis, we propose a model of synthesis-dependent microhomology-mediated end joining (SD-MMEJ), in which de novo synthesis by an accurate non-processive DNA polymerase creates microhomology. Repair junctions with apparent blunt joins, junctional microhomologies, and short indels (deletion with insertion) are often considered to reflect different repair mechanisms. However, a majority of each type had structures consistent with the predictions of our SD-MMEJ model, suggesting that a single underlying mechanism could be responsible for all three. SD-MMEJ is Ku70, Lig4, and Rad51-independent, but impaired in mus308 (POLQ) mutants. Although the SD-MMEJ model is a powerful conceptual tool, the question remained whether or not patterns associated with SD-MMEJ would be found at other DSBs. A meta-analysis of end-joining repair junctions produced in the course of previous studies in Drosophila showed that substantial numbers of the junction sequences had SD-MMEJ consistent repeats. Patterns of repeats varied in a sequence specific manner consistent with the predictions of the SD-MMEJ model. Correlating the patterns of SD-MMEJ consistent repeats at breaks from C-NHEJ proficient and deficient backgrounds with sequence content and break end structure confirms a complex relationship among sequence content, genetic background, and end-joining repair outcome.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Biology.; Advisor: Mitch McVey.; Committee: Susan Ernst, Catherine Freudenreich, Sergei Mirkin, and Maria Jasin.; Keywords: Biology, Genetics, and Molecular Biology.